Voices in a preservice teacher discussion group - Fram-Kulik, Sheila (Colombian Applied Linguistics Journal, 2005)
This discourse analysis study focuses on the dominant voices in a preservice teacher discussion group in a language variation course included in a teacher education program. The voices in the discussion group have what Bakhtin (1981) considers heteroglossic characteristics and what Kristeva (1986) calls intertextuality and what Fairclough (1992) considers interdiscursivity. The analysis of the voices shows textualized voices, that include appropriated voices from mentors or previous teachers that replace the personal voices, at times. The dominant voice of the teacher comes into confl ict with the other dominant voices during discussions. Thus, the relationship of these voices structures the discussion group sessions.